Teacher Autonomy and Technology-Mediated Instruction: Organizational and Social Determinants in Rivers Secondary Schools - Eboh Rhoda Nkemdilim (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
This paper analyses teacher autonomy and the extent of the use of technology in teaching and the social and organizational variables in Rivers State Secondary Schools. Using a descriptive correlational approach, data was gathered from 366 teaching staff in 12 public secondary schools. The results show a statistically significant positive correlation between teacher autonomy and the extent of use of technology in teaching (r = 0.62, p < 0.05). Of the organizational variables, social variables predict teacher autonomy, whereas social variables predict the extent of use of technology in teaching. Self-Determination Theory, Organizational Climate Theory, and TPACK help to unpack the results. The results show that more institutional support and a more collaborative school culture increases the level of digital pedagogy used. The authors call for a more decentralized approach to policy formulation, changes in the way administrators do things and more teacher training.